Mastering primary physical education - Howells, Kristy; Castle, Neil; Little, Rich; Carney, Alison (Physical education teacher) (London New York Bloomsbury Academic, An imprint of Bloomsbury Publishing Plc, 2017)
The Mastering Primary Teaching series provides an insight into the core principles underpinning each of the subjects of the Primary National Curriculum, thereby helping student teachers to 'master' the subjects. This in turn will enable new teachers to share this mastery in their teaching. Each book follows the same sequence of chapters, which has been specifically designed to assist trainee teachers to capitalize on opportunities to develop pedagogical excellence. These comprehensive guides introduce the subject and help trainees know how to plan and teach effective and inspiring lessons that make learning irresistible. Examples of children's work and case studies are included to help exemplify what is considered to be best and most innovative practice in primary education. The series is written by leading professionals, who draw on their years of experience to provide authoritative guides to the primary curriculum subject areas
An introduction to primary physical education -- Current developments in physical education -- Physical education as an irresistible activity -- Physical education as a practical activity -- Skills to develop in physical education -- Developing curiosity and physical development -- Assessing children beyond levels in physical education -- Practical issues
Includes bibliographical references and index
Keywords: Physical education and training -- Study and teaching (Elementary) -- Great Britain; Physical education for children -- Study and teaching (Elementary) -- Great Britain